Cloud Based Medical Image Data Analytics in Healthcare Management - A. Karthika, R; Dhinakaran, K; Poorvaja, D; V. Shanbaga Priya, A (International Journal of Engineering and Technology, 2018)
In todayâ€™s world, the images form a huge amount of unstructured data from the public and the corporate sector. As a result of the growth of these types of data, modern analytical systems need to interpret and assimilate images. This brings in the need of image processing which involves the transformation from images to analytically organized and structured data. It performs required operation on the given input image and returns the related outputs based on the query. Digital image processing has pushed the envelope for the appraisal in various domains such as healthcare, defense and security, remote sensing, robotic visions, pattern recognitions and satellites. The complication involved in the healthcare domain makes it suitable to explore and induce the concept of image processing and increases the potential for prescriptive analytics. The cloud combined with the Image Processing provides the best environment for analyzing these images using the proposed technique. The proposed work involves processing the input images using the cloud data analytics that provides a user-friendly environment and retrieves the relevant images as well as text for the given user query which produces the outputs that are more efficient in terms of parameters like time, size, security and speed comparatively with the existing data mining process.Â Â